Can language modulate perceptual narrowing for faces? Other-race face recognition in infants is modulated by language experience. (March 2022) - Clerc, Olivier; Fort, Mathilde; Schwarzer, Gudrun; Krasotkina, Anna; Vilain, Anne; Méary, David; Lœvenbruck, Hélène; Pascalis, Olivier
Between 6 and 9 months, while infant's ability to discriminate faces within their own racial group is maintained, discrimination of faces within other-race groups declines to a point where 9-month-old infants fail to discriminate other-race faces. Such face perception narrowing can be overcome in various ways at 9 or 12 months of age, such as presenting faces with emotional expressions. Can language itself modulate face narrowing? Many adult studies suggest that language has an impact on the recognition of individuals. For example, adults remember faces previously paired with their native language more accurately than faces paired with a non-native language. We have previously found that from 9 months of age, own-race faces associated with the native language can be learned and recognized whereas own-race faces associated with a non-native language cannot. Based on the language familiarity effect, we hypothesized that the native language could restore recognition of other-race faces after perceptual narrowing has happened. We tested 9- and 12-month-old Caucasian infants. During a familiarization phase, infants were shown still photographs of an Asian face while audio was played either in the native or in the non-native language. Immediately after the familiarization, the familiar face and a novel one were displayed side-by-side for the recognition test. We compared the proportional looking time to the new face to the chance level. Both 9- and 12-month-old infants exhibited recognition memory for the other-race face when familiarized with non-native speech, but not with their native speech. Native language did not facilitate recognition of other-race faces after 9 months of age but a non-native language did, suggesting that 9- and 12-month-olds already have expectations about which language an individual should talk (or at least not talk). Our results confirm the strong links between face and speech processing during infancy.